Vaccines for prevention of HIV infection - Etokidem, Ani (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To evaluate the efficacy and safety of vaccines for the prevention of HIV infection using phase 3 studies.